Sound Absorption of Materials Obtained from the Shredding of Worn Tyres. Issue 4 (December 2014) - Iannace, Gino
The current legislation forbids depositing tyres in landfill at the end of their useful life (European Directive 1999/31 on the landfill of waste). Thus a problem for the reuse of these waste materials arises. One possible use of worn tyres is in the field of applied acoustics. After being shredded, in appropriate particle sizes, it can be possible to reutilise tyres as sound absorbing material. The purpose of this paper is to provide a theoretical model for predicting the sound absorption coefficient of granular materials resulting from the shredding of worn tyres. Starting from the knowledge of the physical properties (such as resistivity, porosity and the structure factor) measured for each range of particle size, by the application of a theoretical model it is possible to obtain the coefficient of absorption of the tested material. Measurements of the absorption coefficient were made using a tube of Kundt, with the use of FFT techniques. Given the dimensions of the tube, the measurements of the absorption coefficient were valid in the range from 200 Hz to 2.0 kHz. Then the theoretical developments were compared with the experimental ones in function of the frequency.